2022
DOI: 10.21744/irjeis.v8n6.2199
|View full text |Cite
|
Sign up to set email alerts
|

Eco enzyme production from fruit peel waste and its application as an anti-bacterial and TSS reducing agent

Abstract: The increasing volume of organic waste in garbage dump facilities will emit methane gas, which is one of the greenhouse gases that cause global warming. By producing eco enzymes from fruit peel and vegetable waste, we can minimize organic waste while also creating beneficial products. In this research, eco-enzyme was produced from papaya, dragon fruit, and orange peel waste mixed with water and molasses. The weight ratio between water, organic compounds, and molasses was 10:3:1. The mixture was fermented for 3… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
1
0
4

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 9 publications
0
1
0
4
Order By: Relevance
“…Limbah domestik memiliki salah satu komponen yang dapat berdampak buruk bagi lingkungan yaitu deterjen atau surfaktan [2]. Pencemaran air berasal dari limbah cair domestik memberikan kontribusi pencemaran air sebesar 87% sementara itu sisanya berasal dari limbah cair industri [3]. Air limbah domestik yang berasal dari usaha laundry berpengaruh terhadap kualitas air tanah, terutama parameter kimia seperti fosfat dan pH [4].…”
Section: Pendahuluanunclassified
See 3 more Smart Citations
“…Limbah domestik memiliki salah satu komponen yang dapat berdampak buruk bagi lingkungan yaitu deterjen atau surfaktan [2]. Pencemaran air berasal dari limbah cair domestik memberikan kontribusi pencemaran air sebesar 87% sementara itu sisanya berasal dari limbah cair industri [3]. Air limbah domestik yang berasal dari usaha laundry berpengaruh terhadap kualitas air tanah, terutama parameter kimia seperti fosfat dan pH [4].…”
Section: Pendahuluanunclassified
“…Penelitian [3] mengkaji dampak eco enzim pada air limbah domestik, untuk menentukan apakah eco enzim membantu atau menghambat penghilangan polutan dalam air limbah domestik. Beberapa kajian menyebutkan eco enzim membantu dekomposisi [27], berfungsi mirip dengan enzim dalam mencapai tingkat degradasi yang lebih tinggi dalam waktu yang lebih singkat untuk air limbah domestik.…”
Section: Gambar 7 Grafik Pengaruh Eco Enzyme Terhadap Kadar Fosfatunclassified
See 2 more Smart Citations
“…After the storage period is reached, the ecoenzyme is harvested by filtering it to obtain the solution (Figure 1). [12] There are some modifications found in processing ecoenzymes, such as in the utilization of type of sugar and fruit/vegetable waste. It was found that the most common types of sugar used are brown sugar, molasses, and jaggery.…”
Section: Production Of Ecoenzymementioning
confidence: 99%